Intertextualidade e produção textual: análise das narrativas do CELLIJ - Edna Mara da Silva de Souza; Odilon Helou Fleury Curado (Universidade do Estado do Rio Grande do Norte, 2013)
The textual construction already stated Bakhtin (2006) is permeated with intertextuality, ie a text takes from other texts, from this perspective, this study examines the intertextuality and the representation of narrative structure presented by students who participated in the workshops creative production of texts after storytime at the Centre for Studies in Reading and Children's and Youth Literature Betty Maria Coelho Silva (CELLIJ) at UNESP campus of Presidente Prudente - SP. This paper presents a reflection on the importance of offering new narratives, whether through storytelling or reading literary texts, to build the child repertoire. From the reading of the corpus nine selected texts, we observed a strong influence of the heroes of commercial films and television series in child production, as well as a tendency writing conditional structure of fairy tales.